GAMBARAN PERSONAL HYGIENE SANTRI PADA KEJADIAN SKABIES DI PONDOK PESANTREN RAUDLATUL MUBTADIIN DESA KUBANG KECAMATAN WANAYASA KABUPATEN BANJARNEGARA TAHUN 2021 - Dwi Atin Faidah (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
Pondok Pesantren Raudaltul Mubtadiin is a boarding school with a high number of scabies incidents, based on data obtained from UPTD Puskesmas Wanayasa 2 the proportion of scabies incidents in 2019 as much as 75%, and in 2020 as much as 82.2%. The purpose of this study is to know the picture of personal hygiene santri on the incident of scabies in Pondok Pesantren Raudlatul Mubtadiin Kubang Village District Wanayasa Banjarnegara Regency in 2021. This type of research is included in descriptive search with cross-sectional methods. The sample of this study is all students who live in boarding schools many as 83. The sampling technique is total sampling, all populations are used as research samples. The data used in this study are primary data obtained from questionnaires and field measurements as well as secondary data from previous studies. Based on the results of research in Pondok Pesantren Raudlatul Mubtadiin most of the students were 13 years old (26.5%), educated islamic junior hight school (60.2%), and the majority of students were female (63.1%). The results of personal hygiene santri category less is 68.7% and proportion of students who have experienced scabies is 71.1%. For boarding schools are expected to provide counseling at the beginning of the arrival of students. For students to improve personal hygiene efforts including skin hygiene, hands, towels, beds, and clothing. For the cottage manager seeks a healthy residence, and maximizes the health post program pesantren.